An epistemic theory of the criminal process, Part II: Packer, Posner and epistemic pressure. (23rd December 2022) - Cullerne Bown, William
Abstract: This is Part II of a novel 'epistemic' theory of the criminal process. Part I, a formal treatment of how poor measurements degrade control over systems of classification, was published in the last issue. This distinguished four distinct realms of control a policymaker may inhabit and established that the criminal process in the USA is trapped in the third best of these, routinely unable to establish that any policy is better than any other. Here, I first use the new epistemic concepts to mathematize Packer's influential 'two models' theory, both a validation of the formal work and a way of giving it traction in the real world. I then use the new techniques to critique Posner's law and economics and reject it on methodological grounds. I then argue that the activity of making policy for the criminal process, including any quantativity, is largely a form of ritual. The function of this has been to keep at bay an enduring pressure for rationality, as in Weber's rationalization thesis, that could not be satisfied. Now that we have the capacity for better measurements, a rational approach is for the first time attainable, and I contemplate the end of the old order.